Demand for applications in service industries. - MILES, Ian (1995)
Focuses on two IT-intensive services, viz., office and related service activities, which is a major user of hardware and software; and computer services, which also plays a major role in the evolution of hardware and software. Points out that technical and organizational changes are now commonplace in both of these sectors, which are gaining economic prominence, and indicates the ways in which many other service activities are likely to develop.